(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The complexes of the type MLCl¬2, where M = Co(II), Cu(II), Ni(II), Zn(II), Cd(II) and Hg(II) and L is the thiosemicarbazide ligands derived from reaction between 3-methoxybenzofuran-2-carboxyhydrazide and phenylisothiocynate (MBCPT) / p-chlorophenylisothiocynate (MBCClPT). All the complexes were characterized on the bases of elemental analysis, conductance, magnetic susceptibility measurements, UV-Vis, IR, 1H NMR, ESR spectra studies and X-ray data studies. Thiosemicarbazide ligands behave as bidentate by coordinating through the oxygen of the carbonyl group and the nitrogen of the hydrazide residue. Based on the results, we have proposed the probable structures for all the metal complexes. Both the ligands and their complexes have been screened for their fungicidal and bactericidal activities